Selling Orientation – Customer Orientation (S.O.C.O): Hubungan Penerapannya dalam Meningkatkan Kinerja Salesperson di Kota Palu - Revan, Revan; Ponirin, Ponirin; Rombe, Elimawaty; Auriza, Mohammad Zeylo (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study aims to analyze the influence of selling orientation and customer orientation in their application to improve salesperson performance in Palu City. The population of this quantitative-associative study is all salespersons in Palu City, with a sample size of 85 respondents selected through purposive sampling techniques. Data collection using a questionnaire instrument in the form of a Google form. The research data analysis method uses Jeffreys's Amazing Statistics Program. The results of this study indicate that selling orientation does not have a significant effect on salesperson performance; on the contrary, customer orientation has been shown to have a significant effect on salesperson performance. Simultaneously, however, there is a significant influence between the application of selling orientation and customer orientation on improving salesperson performance in Palu City compared to the application of each orientation partially.